Soluble urokinase-type plasminogen activator receptor and urokinase-type plasminogen activator receptor contribute to chemoresistance in leukemia - Guo, Hong (Oncol Lett, 2017)
The soluble urokinase-type plasminogen activator receptor (suPAR) and the urokinase-type plasminogen activator receptor (uPAR) have been proposed as useful biomarkers of tumor progression. Recently, suPAR was associated with chemoresistance in lung cancer. However, its clinical significance in leukemia has not previously been investigated. The present study examined the plasma levels of suPAR and the expression of the uPAR on bone marrow (BM) cells in 86 patients with leukemia at diagnosis prior to chemotherapy and 26 normal subjects (control group). The plasma suPAR levels were measured using ELISA, whilst uPAR expression was assayed by flow cytometry analysis. In addition, cell surface uPAR expression on K562 and multidrug-resistant K562/ADM cell lines was studied by western blotting. On admission and follow-up, the levels of suPAR in patients with leukemia were significantly increased compared with controls. Systemic levels of suPAR were strongly associated with the numbers of white blood cells. A case was defined as uPAR-positive (uPAR+) if >20% of the gated cells expressed uPAR. In comparison with 26 healthy BM samples that were negative for uPAR expression, 48 (55.8%) of the 86 leukemia patients were uPAR+. uPAR expression on the cell surface of multidrug-resistant K562/ADM cells was increased compared with that on K562 cells. In conclusion, plasma suPAR expression may be a useful marker for subtype classification of patients with leukemia and cell surface uPAR may be associated with resistance to chemotherapy or disease progression.